Peran Pendeta dalam Pemilihan Presiden di Indonesia Menurut Sudut Pandang Alkitab - Miraniat Hati Gulo (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The presidential election in Indonesia is an important moment for citizens, including Christians, who cannot escape the influence and spiritual direction of pastors. Although the Bible does not directly address modern presidential elections, its moral principles provide a foundation for pastors to provide guidance to their congregations. Through an understanding of the Bible, pastors can guide their congregations to consider moral values in choosing leaders, in accordance with the principles of justice, truth, and responsibility to others and God. Pastors not only lead spiritually, but also as moral counsellors who instil spiritual and civic responsibility. They also serve as prayer warriors, guiding the selection of leaders with character and responsibility, according to biblical principles. The moral responsibility of leaders, peace, unity, and reconciliation are the focus of pastors' guidance to their congregations. Pastors are expected to provide an understanding of the ideal leader, in accordance with biblical principles. This study explores the role of pastors in Indonesia's presidential election from a biblical perspective, highlighting their moral responsibility, voting based on biblical principles, and their role in promoting peace and unity amidst political differences.